The Genus Berberis Linn.: A Review - R, Rashmi; Rajasekaran, A.; Pant, Jagdish (Pharmacognosy Reviews)
Berberis Linn. (Family: Berberidaceae), a genus of shrubs or small tress, distributed in the temperate and sub-tropical parts of Asia, Europe and America. The genus consists of species which are commonly used in many traditional systems of medicines. About seventy seven species are reported from India. The crude extracts of various parts and pure isolates of Berberis species were reported to possess hypoglycemic, anticancer, gastro irritant, antifatigue, anticoagulant, antipyretic, local anesthetic, antiprotozoal, antibacterial, hypotensive, anti-inflammatory and CNS-depressant activities. Berberis species have been found to possess tonic, stomachic, astringent, antiperiodic, diaphoretic properties and are also useful in the treatment of jaundice, enlargement of spleen etc. The widespread uses of Berberis species in traditional systems of medicine have resulted in their extensive chemical analysis for their bio-active principles. The comprehensive compilation of the chemical constituents isolated from Berberis species covering the literature up to 2007 is presented in this paper. This article briefly reviews the botany, chemistry and pharmacology of Berberis species.
Keywords: Berberidaceae; Berberis aristata; berberine; pharmacology; chemical constituents